2008
DOI: 10.1093/jnci/djm328
|View full text |Cite
|
Sign up to set email alerts
|

Mutant FLT3: A Direct Target of Sorafenib in Acute Myelogenous Leukemia

Abstract: Sorafenib may have therapeutic efficacy in AML patients whose cells harbor FLT3-ITD mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
280
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(289 citation statements)
references
References 40 publications
8
280
0
1
Order By: Relevance
“…Although sorafenib responses in FLT3-ITD AML patients are usually transient, 11,13,14,16 we and others have previously published several cases with relapsed FLT3-ITD AML who showed extended remissions under sorafenib monotherapy. 17,[18][19][20][21][22][23] This stimulated us to gain a better understanding of the value of sorafenib monotherapy in FLT3-ITD AML-in particular with respect to the circumstances where complete and long-lasting remissions may be obtained.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although sorafenib responses in FLT3-ITD AML patients are usually transient, 11,13,14,16 we and others have previously published several cases with relapsed FLT3-ITD AML who showed extended remissions under sorafenib monotherapy. 17,[18][19][20][21][22][23] This stimulated us to gain a better understanding of the value of sorafenib monotherapy in FLT3-ITD AML-in particular with respect to the circumstances where complete and long-lasting remissions may be obtained.…”
Section: Introductionmentioning
confidence: 91%
“…[8][9][10] For example, in the first phase I trial, testing the FLT3 inhibitor sorafenib (Nexavar, formerly BAY 43-9006) in AML only FLT3-ITD-positive (FLT3-ITD), but not FLT3-ITD-negative AML patients responded. 11 Three subsequent phase I studies underscored this evidence by demonstrating consistent activity of sorafenib in relapsed and refractory FLT3-ITD AML, while primary resistance was frequently seen in AML expressing the wild-type form of FLT3. [12][13][14] Thus, although sorafenib simultaneously blocks FLT3 and multiple other kinases, such as the serine threonine kinase Raf-1, plateletderived growth factor receptor and vascular endothelial growth factor receptor, 15 its most relevant target in AML appears to be FLT3-ITD.…”
Section: Introductionmentioning
confidence: 97%
“…115 RAF can be inhibited by sorafenib. Sorafenib also targets FLT3-mutated AML cells, 116 and current phase-I/II trials are ongoing in AML. 117,118 Inhibitors of MEK have been developed that sensitize leukemic blast cells to other drugs, for example, arsenic trioxide and demethylating agents.…”
Section: Toward Targeted Therapymentioning
confidence: 99%
“…[10,11] It has been reported that sorafenib induced death of cells that expressed the FLT3-ITD or FLT3-D835G but not cells that expressed the FLT3-D835Y point mutant or wild-type FLT3 in vitro. [12] However, we report here the successful complete remission induction by sorafenib monotherapy in a FLT3-D835Y-positive patient with refractory AML-M5 followed by allogeneic stem cell transplantation. Though duration of sorafenib was quite short, it is hard to achieve completion remission for him only with the late effect of previous combined chemotherapies.…”
Section: Discussionmentioning
confidence: 85%